Vanadium oxide thin film deposited on Si by atomic layer deposition for non-volatile resistive switching memory devices - Lee, Wanggon; Iqbal, Shahid; Kim, Jisu; Lee, Sangmin; Lee, Jinchan; Kumar, Mohit; Seo, Hyungtak (Applied Surface Science, 2023)
Vanadium dioxide (VO2) is a representative metal–insulator-transition (MIT) material that undergoes a reversible phase transition at 68 °C, which is close to room temperature. This shows the bias-triggered volatile resistance changes driven by MIT so that many studies have been made to implant VO2 as selectors for solving the sneak current problem of resistive random-access memory (ReRAM). However, the non-volatile switching of VO2 for non-volatile memory (NVM) application has not been demonstrated yet but if realized, this is truly breakthrough for low power and ultrafast NVM application. Herein, we report a successful formation of multiphase vanadium oxide on Si wafer via atomic layer deposition followed by a post-deposition annealing (PDA) process and demonstrate its applicability as a NVM device. It was confirmed that the multiphase vanadium oxide has MIT-driven abrupt resistance switching (i.e., low- and high-resistance state) at ± 1.6 V due to increased oxygen vacancies responsible for non-volatile memory property. The alternating current (AC) endurance upto 30,000 cycles and charge retention upto 3,000 sec are achieved at 2ⅹ102 of LRS/HRS current ratio. As a result, it opens the possibility of application to next-generation memory devices by reliable non-volatile MIT switching scheme.
Keywords: Atomic layer deposition; Atomic-layer deposition; Metal-to-insulator transition; Metal-to-insulator transitions; Multiphases; Non-volatile memory; Non-volatile-memory applications; Nonvolatile; Vanadium oxide thin films; VO 2 thin films; Atomic layer deposition (ALD); Metal-to-insulator transition (MIT); Non-volatile Memory; VO2 thin film